Abuse Potential of Lemborexant, a Dual Orexin Receptor Antagonist, Compared With Zolpidem and Suvorexant in Recreational Sedative Users. Issue 4 (24th July 2022) - Landry, Ishani; Hall, Nancy; Aluri, Jagadeesh; Filippov, Gleb; Reyderman, Larisa; Setnik, Beatrice; Henningfield, Jack; Moline, Margaret
Abstract: Background: Lemborexant (LEM) is a dual orexin receptor antagonist approved for the treatment of insomnia in adults in multiple countries including the the United States, Japan, Canada, Australia and several Asian countries. Procedures: This was a randomized, single-dose, single-center, double-blind, active-control, 6-way crossover study to evaluate LEM abuse potential. The study assessed oral doses of LEM 10 mg (LEM10), 20 mg (LEM20), and 30 mg (LEM30) compared with placebo (PBO), zolpidem (ZOL) immediate release 30 mg, and suvorexant (SUV) 40 mg. Subjects were healthy, nondependent, recreational sedative users able to discriminate/like the effects of both SUV and ZOL from PBO during a qualification phase. Results: Abuse potential endpoints were analyzed in qualified subjects who received and completed all treatments (n = 32). On the "at this moment" drug-liking visual analog scale (VAS), mean maximum (peak) effect (primary endpoint) values were 78.4, 80.5, and 83.6 for LEM10, LEM20, and LEM30, respectively, which were all significantly greater than PBO (57.8; all P > 0.05) but not different from SUV (76.1) or ZOL (78.3). Similarly, for secondary endpoints overall drug-liking VAS and take-drug-again VAS, mean maximum (peak) effect values for all LEM doses were significantly greater than PBO ( P > 0.05) but not different compared with ZOL or SUV. Conclusions: For all doses, LEM demonstrated abuse potential versus PBO and appeared to have a similar abuse potential profile to ZOL and SUV in this study population. Lemborexant was well tolerated. Lemborexant has been placed in Schedule IV, the same drug schedule as ZOL and SUV.